Emergent Theories and Practices in Accounting Proceedings of the International Management Accounting Conference 5, 19 - 21 October 2009, Cititel Mid Valley, Kuala Lumpur - International Management Accounting Conference Kuala Lumpur) (Kuala Lumpur : Universiti Kebangsaan Malaysia, 2009)
Due to the overwhelming response received in the previous IMACs, the Faculty is once again organizing IMAC V on the 19-21 October 2009. The theme for the upcoming event is 2Emergent Theories and Practices in Accounting3. The keynote speaker is Professor Robert Chenhall from Monash University, Australia. In line with the conference theme, IMAC V hopes to enrich the knowledge sharing experience by inviting practicing accountants as speakers in each of the concurrent session
Keywords: Accounting -- Congresses